PENILAIAN UNJUK KERJA PT. X & PT. Y BERDASARKAN METODE BENCHMARKING - sulistyadi, Kohar; Ismara, Yudhi (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2015)
Many ways to assess the performance of a company, in this case the shoe company needs to  create  value  advantages  for  consumers,  some  of  the  factors  that  support  for  the achievement of the efficiency value, mimimasi costs, business competence, the demands of a dynamic market. to get a gap value of each companys performance on a benchmarking approach  is  needed.  Benchmarking  is  a  continuous  process  of  measuring  products, services and practices against the toughest competitors a recognized risk management.The  purpose  of  this  paper  are  :  (1).  Finding  an  effort  to  catch  up  with  PT.  Y  should improve  performance  for  changes  and  improvements,  based  on  the  destination  map balance (parity goal) with the assumption that it takes three years to equalize with PT Y with the aim of: (a) the first six months of the formation of the team for the analysis of constraints,  (b)  testing  the  application  of  the  second  six-month  evaluation,  and  (c)  the periodic  application;  (2).  Designing  a  proposal  to  replace  the  conventional  purchase procedures; (3). Training for increased performance human resources; and (4). Evaluate the improvement of all activities with the benchmarking approach.The  end  result  is  to  get  the  value  of  the  performance  of  competitors,  comparing  the position of some elements between the two companies is based on: (a) technical quality, (b) speed of the material arrival time, (c) value reliability, and (d) evaluation of suppliers.Key Words : Benchmarking, performance gap